Pengetahuan Ibu Dalam Upaya Pemberian Imunisasi Dasar Pada Anak Di Kepulauan Manipa Tahun 2021 - Rusnani Martahan; Zubaeda Zubaeda (Pusat Riset dan Inovasi Nasional, 2023)
Immunization is one of intervention to give immune for the baby/child with the procedure input vaccine into the body so the body could make antibody against to disease spesificly. Immunization services for baby/child at Manipa Islands 2021 have not yet reached Universal Child Immunization. It was mean more than 90% had achieved. They are BCG (50%), DPT (40%), Hepatitis B (20%), Polio (60%) and Campak (10%). The aim of this research to know between knowledge with mother’s effort for giving immunization in children at Manipa Islands 2021. This research is analysis description with cross sectional study. All of mothers who have child 12-23 month at Manipa Islands 2021, as respondent have taken by total sampling (30 respondent) and used chi-square with significant level α=0,055. Result of research has showed that there was relationship between knowledge with mother’s effort for giving immunization. Knowledge p=0,010,. For respondent to more interesting in giving immunization for children base on their ages to protection from some disease.